Universities and their commitment with knowledge, science and technology - Núñez Jover, Jorge (Revista Universidad de Guayaquil, 2012)
In this paper we argue that public universities in Latin America and the Caribbean must be important actors in the development of knowledge, science, technology and innovation. We also suggest that universities must develop research and postgraduate programs in Science and Technology Studies, which must contribute to the public policies and culture of our countries.
Keywords: University; science; technology